Chemical Characteristics of Ore-Bearing Intrusions and the Origin of PGE–Cu–Ni Mineralization in the Norilsk Area - Nadezhda Krivolutskaya; Sheida Makvandi; Bronislav Gongalsky; Irina Kubrakova; Natalia Svirskaya (Minerals, 2021)
The composition of the parental magmas of Cu–Ni deposits is crucial for the elucidation of their genesis. In order to estimate the role of magma in ore formation, it is necessary to compare the compositions of silicate rock intrusions with different mineralization patterns, as observed in the Norilsk region. The rock geochemistry of two massifs located in the same Devonian carbonate rocks—the Kharaelakh intrusion, with its world-class platinum-group element (PGE)–Cu–Ni deposit, and the Pyasinsky-Vologochansky intrusion, with its large deposit—was studied. Along with these massifs, the Norilsk 2 massif with noneconomic mineralization intruded in the Ivakinskaya-Nadezhdinskaya basalts was studied as well. Their settings allow the estimation of the parental magma composition, taking into account the possible assimilation of host rocks. Analyses of 39 elements in 97 samples demonstrated the similarity of the intrusions in terms of their major components. The Pyasinsky-Vologochansky intrusion contains the highest trace element contents compared with the Kharaelakh and Norilsk 2 massifs, evidencing its crystallization from evolved parental magma. No influence of host rocks on the silicate rock compositions was found, except for narrow (1–2 m) endo-contact zones. There is no correlation between the mineralization volume and the rock compositions of the studied intrusions. It is assumed that the intrusions were formed from one magma crustal source irregularly rich in sulfur (S). This source inhomogeneity in terms of the sulfur distribution resulted in deposits of varying sizes. The magmas served as a transporting agent for sulfides from deep zones to the surface.